2014 16th International Power Electronics and Motion Control Conference and Exposition 2014
DOI: 10.1109/epepemc.2014.6980537
|View full text |Cite
|
Sign up to set email alerts
|

DSP based embedded code generation for PMSM using sliding mode controller

Abstract: This study presents a Digital Signal Processor (DSP) based embedded code generation which is obtained automatically in PSIM software for Permanent Magnet Synchronous Motor (PMSM) control system. The simulation model of the PMSM control system is developed in PSIM environment using Motor Control Blocks and Embedded Target for TI 28335 block. This control block diagram is send to SimCoder to generate C-code that is ready to run on the DSP hardware, SimCoder also creates the complete project files for the TI Code… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
0
5
0
1
Order By: Relevance
“…Mehmood ve Jawawi (2011), ilgiye yönelik kod üretim yaklaşımlarını bir inceleme çalışma kapsamında ele almış, çoğu yaklaşımın sınıf diyagramlarına odaklandığını raporlamış, davranış diyagramlarının da dikkate alınarak tam kod üretiminin mümkün olabileceğini ifade etmiştirler [15]. Morkoç ve arkadaşları (2014), kalıcı mıknatıslı senkron motorun (PMSM) kontrol sistemi için DSP tabanlı gömülü kod üretim yazılımı geliştirmişlerdir ve bu sistem sayesinde, prototipleme kolaylaşmış, geliştirme süreleri kısalmıştır [15]. Wang ve arkadaşları (2012), türetim kurallarına dayalı olarak kod üretiminin gerçekleştirilebileceğini ifade ederek bu yönde bir modelleme metodu önermiştir [16].…”
Section: şEkil 2 Kod üReticinin Dahil Olduğu Durumda Kodlama Iş Akışunclassified
“…Mehmood ve Jawawi (2011), ilgiye yönelik kod üretim yaklaşımlarını bir inceleme çalışma kapsamında ele almış, çoğu yaklaşımın sınıf diyagramlarına odaklandığını raporlamış, davranış diyagramlarının da dikkate alınarak tam kod üretiminin mümkün olabileceğini ifade etmiştirler [15]. Morkoç ve arkadaşları (2014), kalıcı mıknatıslı senkron motorun (PMSM) kontrol sistemi için DSP tabanlı gömülü kod üretim yazılımı geliştirmişlerdir ve bu sistem sayesinde, prototipleme kolaylaşmış, geliştirme süreleri kısalmıştır [15]. Wang ve arkadaşları (2012), türetim kurallarına dayalı olarak kod üretiminin gerçekleştirilebileceğini ifade ederek bu yönde bir modelleme metodu önermiştir [16].…”
Section: şEkil 2 Kod üReticinin Dahil Olduğu Durumda Kodlama Iş Akışunclassified
“…Considering the complexity of control systems and the need for quick experimentation, a prior study developed a rapid control prototype for PMSM utilizing a digital signal processor (DSP) in conjunction with the PLECS software [12]. A subsequent study [13] reported on DSP-based embedded code generation via MBD to be achieved automatically using PSIM software for the control system of a PMSM. The speed control of a PMSM has been demonstrated by integrating a field-oriented control (FOC) algorithm with the MBD in MATLAB by using TI digital motor control, IQ math, and embedded coder Texas C2000 processor library [14].…”
Section: Introductionmentioning
confidence: 99%
“…Paper [37] discusses how the code generation capabilities of MATLAB/Simulink can be applied in the development process of critical embedded systems. Code generation applied in controller development of PMSMs is discussed in [38].…”
Section: Introductionmentioning
confidence: 99%